Determinants of Functional Difficulty among Women in Nepal: A Cross-sectional Study - Adhikari, Anuska; Acharya, Devraj; Adhikari, Ramesh (Janapriya Journal of Interdisciplinary Studies, 2023)
This study explores the situation of women with functional difficulties in Nepal and identifies key determinants contributing to their challenges. Utilizing data from the 2019 Multiple Indicator Cluster Survey, the research examines the association of various factors with functional difficulties among a sample of 13,255 married women aged 18 to 49. The results reveal significant associations between province, age, education, and media exposure with functional difficulties. Wealthier women and those with higher education exhibit lower odds of experiencing functional difficulties, while women aged 35 and above and those with medium or high media exposure demonstrate higher odds. The study highlights the limited access to healthcare and rehabilitation services, social stigma and discrimination, and high levels of poverty and unemployment faced by women with functional difficulties in Nepal. By shedding light on these issues, this research aims to provide valuable insights for policymakers, healthcare providers, and disability rights advocates, fostering improvements in the lives of women with functional difficulties in Nepal.